SENSORY EVALUATION FOR CONSUMER ACCEPTANCE TESTING OF MEATBALL MADE FROM MIXED OF BEEF AND FRESHWATER MUSSEL MEAT (Plisbryoconcha exilis) - Nalurita Nalurita; Bustari Hasan; Dian Iriani (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACT This study was aimed to determine of sensory evaluation for consumer acceptance on meatball made from a mixture of beef and freshwater mussel meat (Plisbryoconcha exilis). The method used was an experimental method with the addition mixed of beef and freshwater mussel meat into meatball consisting of 5 levels treatment: B0 (0%:100%), B1 (15%:85%), B2 (30%:70%), B3 (45%:55%), and B4 (100%:0%). A Completely Randomized Design (CRD) as an experimental design with 3 replicated. The parameter tested was sensory evaluation (consumer acceptance) for appearance, aroma, taste, and texture with 80 untrained panelists, using a 9 point hedonic scale. The results showed that the meatball made from mixture of beef and freshwater mussel meat 45%: 55% (B3 treatment) was the best treatment with overall likability 35% panelists (28 panelists), for overall acceptability was 100%, wherein appearance 7.98 (brilliant and intact meatball), aroma 7.75 (distinctive aroma of mixed beef and freshwater mussel meat), taste 8.32 (very tasteful), texture 7.61 (very thick and dense texture). Statistical analysis of meatball made form a mixture of beef and freshwater mussel meat was significantly different among treatment with 95% of confidence level.Keywords: Meatball, beef, freshwater mussel meat, consumer acceptance